2022
DOI: 10.1177/00469580221081445
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Healthcare Provision During Covid-19 and Their Impact on Children With Chronic Illness: A Scoping Review

Abstract: This paper provides an overview of the evidence around how the health systems and policy response to the Covid-19 pandemic affected children with long-term conditions in the UK. We conducted a scoping review guided by the PRISMA-ScR Checklist. The PubMed and PsycINFO databases (2019-August 2021) were searched and screened for papers (of any design) by 2 reviewers independently. The electronic database search was supplemented by manual searching. A total of 32 papers were identified, including studies on UK pae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 37 publications
0
22
0
3
Order By: Relevance
“…Specific recommendations established from the guidelines such as prioritization of high-grade malignancy, as well as other aspects such as lockdowns, social restrictions, restructure of cancer care with prioritization of high-risk malignancies and use of telemedicine, fear of infection, financial distress and shortage in medications could explain the delays and cancellation in cancer treatment, screening and diagnosis reported in several studies. For example, Lignou S et al 202 38 raised concerns that use of telehealth for people with cancer suggests a greater proportion of missed diagnoses. Most of examined systematic reviews reported a substantial reduction in treatment, screening, and diagnosis of several cancers during the pandemic, which was more pronounced for countries that implemented a lockdown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific recommendations established from the guidelines such as prioritization of high-grade malignancy, as well as other aspects such as lockdowns, social restrictions, restructure of cancer care with prioritization of high-risk malignancies and use of telemedicine, fear of infection, financial distress and shortage in medications could explain the delays and cancellation in cancer treatment, screening and diagnosis reported in several studies. For example, Lignou S et al 202 38 raised concerns that use of telehealth for people with cancer suggests a greater proportion of missed diagnoses. Most of examined systematic reviews reported a substantial reduction in treatment, screening, and diagnosis of several cancers during the pandemic, which was more pronounced for countries that implemented a lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Lignou S et al 2022 38 reported that between 18 th to 31 st of January 2021, pediatric and noncancer surgical activities were occurring at less than a third of the rate of the previous year, while Di Cosimo SD et al 2022 34 reported cancellation/delays of treatment in 58% (95%CI, 48%-67%; I 2 , 98%) of centers. Majeed A et al, 2022 14 showed that shortage of treatment and delays and interruptions to cancer therapies in general were more common in low-and middle-income countries.…”
Section: Delayed And/or Cancelled Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable children with chronic illness to escape from corrosive vulnerability in the aftermath of the pandemic and the different kinds of harm that would result from it, factors that create and sustain vulnerabilities and harm need to be critically evaluated and addressed. This suggests that different types of evidence are important (Lignou et al 2022 ) to inform policies in addressing the longer-term impact of Covid-19 on child health and plans for future pandemics, and for identifying strategies that can eliminate systemic weaknesses in meeting the complex needs of children with chronic conditions more generally.…”
Section: Ethical Responses To Children’s Increased Vulnerabilities In...mentioning
confidence: 99%
“… 2 Redirection of medical and human resources to providing pandemic services and the importance of protecting the patients and health workers led to the suspension of unurgent treatments. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%